Political awareness in the digital era: How social media drives community engagement for development in Nigeria - Inobemhe, Kelvin (IAIN Madura, 2025)
This study was conducted to examine social media, herein referred to as SM-driven community engagement, and its role in political awareness creation towards socio-political development in Nigeria. The rationale behind the study was the need for insights as to the place of SM engagement in political awareness creation. The researcher relied on a survey research design using a multistage sampling technique to determine the final population sample for the survey. A Google Forms-aided questionnaire was designed, and a link was shared with the respondents. The findings of the study show greater access to SM platforms among Nigerians, with political information as one of the most prominent contents. SM-disseminated political information creates awareness as youth with greater access become interested in political matters on account of their exposure to such information across platforms. Furthermore, the study also shows that community engagement is enhanced by virtue of the use of SM for political awareness creation. It was also revealed that the capacity of SM as platforms for awareness creation drives community engagement and development in Nigeria. This is particularly the case with respect to the development of political consciousness towards meaningful participation in the political sphere. The researcher concluded that SM-driven political awareness creation creates informed citizens capable of making decisions from an informed perspective toward the development of society in the current digital era.